HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU AGRESIF ANAK USIA 3-4 TAHUN DI KELOMPOK BERMAIN SAYANG BUNDA DESA SRI GADING KECAMATAN LUBUK DALAM KABUPATEN SIAK - Kristiani, Vernanda Ririk Dwi; Novianti, Ria; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACT : This research purpose to know correlation between parent care for pattern with Aggressive Behavior children 3-4 year at Play Group Sayang bunda of Sri Gading subdistrict Lubuk In Siak. The rsearch design is correlation quantitative approach. The research data get from questionnaire consist of 36 items. Then, the researcher divide questionnaire to 30 samples who have set in to get reseach data. To know visible image Aggressive Behavior of child obtainable from questionnaire result by 10 items expression that divide to 30 samples with score each answer to always gived score 4,often gived score 3, seldom gived score 2 and never gived score 1. The level correlation between parent care for pattern authoritative with Aggressive Behavior of children 3-4 year at Play Group Sayang bunda of Sri Gading subdistrict Lubuk dalam Siak regency middle category is 0.673. the level correlation between parent care for pattern democratic with Aggressive Behavior of children 3-4 year at Play Group Sayang bunda of Sri Gading subdistrict Lubuk dalam Siak reside in the strong category is 0.853. the level correlation between parent care for pattern permisif with Aggressive Behavior of children 3-4 year at Play Group Sayang bunda of Sri Gading subdistrict Lubuk dalam Siak in middle category is 0.573. So, the researcher can conclude that hipotesis the correlation between parent care for pattern with Aggressive Behavior of children 3-4 year is accepted.Keyword: parent care for pattern, Aggressive Behavior.